A stepped frequency continuous wave short range radar for agriculture measurements with coherent cancellation calibration - Peterson, Garrett Sidney (Kansas State University, 2020)
Leakage/crosstalk in short-range compact radar systems is an issue that is gaining importance as these systems proliferate our society. Leakage and crosstalk in these radars result from three primary sources: antenna, board level, and component level coupling. This leakage/crosstalk often manifests as false targets at the output. Several strategies have been proposed to reduce the effects of these coupling paths. They involve RF cancellation at the frontend of the system, digital cancellation in the backend, or clever antenna placement. All these solutions have limited effectiveness but can be acceptable in given use cases. This thesis looks at the sources of the leakage/crosstalk and the magnitude each source contributes. It discusses previous research into line isolation to show what can lead to good design decisions and proposes a new method of mitigation that involves injection of a correction signal using the coherent cancellation calibration technique. This technique focuses on short-range stepped frequency continuous wave radar systems. The technique was evaluated through the development and testing of a compact short-range system for agricultural purposes. The K-State agricultural radar shown went through several revisions and resulted in a compact light-weight sensing radar that shows promise as a sensor for precision agriculture uses. This thesis documents design decisions made in development to produce a radar that can effectively cancel large amounts of self-interference resulting from antenna coupling and mixer leakage. The field experiments show results for measuring crop height and have potential to provide additional data such as yield and biomass estimates.
Keywords: Radar; Crosstalk; Agriculture; Coherent cancellation calibration; Self-interference